2017
DOI: 10.1038/srep45556
|View full text |Cite
|
Sign up to set email alerts
|

Scaling trends and performance evaluation of 2-dimensional polarity-controllable FETs

Abstract: Two-dimensional semiconducting materials of the transition-metal-dichalcogenide family, such as MoS2 and WSe2, have been intensively investigated in the past few years, and are considered as viable candidates for next-generation electronic devices. In this paper, for the first time, we study scaling trends and evaluate the performances of polarity-controllable devices realized with undoped mono- and bi-layer 2D materials. Using ballistic self-consistent quantum simulations, it is shown that, with the suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…2D semiconductors are well-suited for this purpose, as the existence of a band gap permits the material to be depleted of charge carriers. For example, it is observed that a high semiconducting band-gap (∼1.5 eV and 1.1 eV, respectively) prevents achieving high ON-currents in mono-and bi-layer WSe 2 [19]. This can be seen in Table ??…”
Section: Multilayer Tmdfetsmentioning
confidence: 92%
“…2D semiconductors are well-suited for this purpose, as the existence of a band gap permits the material to be depleted of charge carriers. For example, it is observed that a high semiconducting band-gap (∼1.5 eV and 1.1 eV, respectively) prevents achieving high ON-currents in mono-and bi-layer WSe 2 [19]. This can be seen in Table ??…”
Section: Multilayer Tmdfetsmentioning
confidence: 92%
“…The control gate (CG), in the inner region, regulates the channel conduction, whereas the polarity gate at source (PGS) and the polarity gate at drain (PGD) modulate the Schottky barrier to, respectively, allow electrons or holes to flow into the channel. This technology has been demonstrated in the literature with multiple channel geometries and materials, such as silicon nanowire structures [10], [12], silicon fin structures [13], 2-D materials [14], [16], [17], and carbon nanotubes [18]. In addition, performance at aggressive scaling nodes was estimated using ballistic selfconsistent quantum simulations [17] on 2-D materials from the transition-metal-dichalcogenide family and showed possibilities for TIGFETs to achieve high-current densities.…”
Section: A Generalitiesmentioning
confidence: 99%
“…This technology has been demonstrated in the literature with multiple channel geometries and materials, such as silicon nanowire structures [10], [12], silicon fin structures [13], 2-D materials [14], [16], [17], and carbon nanotubes [18]. In addition, performance at aggressive scaling nodes was estimated using ballistic selfconsistent quantum simulations [17] on 2-D materials from the transition-metal-dichalcogenide family and showed possibilities for TIGFETs to achieve high-current densities. Fully exploiting a doping-free process, TIGFETs also bear the promise of improved robustness to process variations as identified in [19].…”
Section: A Generalitiesmentioning
confidence: 99%
“…A solution for thus enhancing the device performance and their extreme thinness alleviate shortchannel effects with this technology [17], the fabrication of double gate device which need complicated technology and has been not deserving a complete special attention irrespective has been very expensive [18].…”
Section: Introductionmentioning
confidence: 99%